Screening for High Blood Pressure at the Dentist’s Office - Abdulwahab M; Kamal M; Akbar A (Dove Medical Press, 2022)
Mohammad Abdulwahab, Mohammad Kamal, Ali Akbar Department of Surgical Sciences, Faculty of Dentistry, Health Sciences Center, Kuwait University, Jabryia, KuwaitCorrespondence: Mohammad Abdulwahab, Department of Surgical Sciences, Faculty of Dentistry, Health Sciences Center, Kuwait University, Jabryia, Kuwait, Tel +965-978-95760, Email mabdulwahab@hsc.edu.kwBackground: High blood pressure is a worldwide issue that can go undetected. Many are unaware of such a problem due to the lack of symptoms in early stages. Visiting the dentist can be a good place to screen for such health issues. Screening dental patients at every dental visit can be of great benefit. The aim of this study was to determine if screening for blood pressure at the dental office is efficient and beneficial for patients.Methods: The HEYER VizOR Digital Blood Pressure Monitor was used to measure the blood pressure of all the patients visiting the dental clinic, ranging in age from 18 to 85. The study was comprised of patients who had never been diagnosed as hypertensive by a physician or if they had been diagnosed before.Results: A total of 273 participants met the inclusion criteria. One hundred and thirty-seven (50.1%) patients had high blood pressure readings compared to 136 (49.8%) patients with normal blood pressure readings. It also showed that 54 (38%) of patients with high blood pressure readings had never been diagnosed by a physician with hypertension and were unaware of their blood pressure status. In addition, 83 (63.3%) of patients who had been diagnosed with hypertension by a physician had high blood pressure readings. The data also showed that 5.3% of patients diagnosed by their physician do not take their prescribed medication.Conclusion: In this study, we showed that screening blood pressure at the dental office can detect high blood pressure readings in dental patients. It is also a useful screening tool for blood pressure for diagnosed and undiagnosed patients. Screening dental patients at the dental office is a useful tool that can help in the screening for blood pressure and should be implemented at every visit.Keywords: dental office, diastolic blood pressure, health care, medication, systolic blood pressure